Feeding Anglo-Saxon England: the bioarchaeology of an agricultural revolution. (10th April 2019) - Hamerow, Helena; Bogaard, Amy; Charles, Mike; Ramsey, Christopher; Thomas, Richard; Forster, Emily; Holmes, Matilda; McKerracher, Mark; Neil, Samantha; Stroud, Elizabeth
Abstract: Abstract : The early Middle Ages saw a major expansion of cereal cultivation across large parts of Europe thanks to the spread of open-field farming. A major project to trace this expansion in England by deploying a range of scientific methods is generating direct evidence for this so-called 'Medieval Agricultural Revolution'.